MOTIVASI KERJA APARATUR SIPIL NEGARA PADA BADAN LINGKUNGAN HIDUP KOTA PALU - Moiga, Jefri Mito (Katalogis, 2018)
This study aims to provide an overview of how the motivation of the State Civil Apparatus at the Environmental Agency of Palu City. Informants in this study amounted to 10 peoples and a key informant (key informant). Data analysis techniques as well as the usual qualitative researchs, such as data reduction, data presentation, and conclusions. The results showed that: in the drive for achievement, employees strive to achieve the highest achievement; the problem is still the lack of fulfillment of facilities and infrastructure where the status of the office is still contract, as well as awards in the form of additional income and bonuses. In addition to the aspect of the drive to power, employees have the motivation to influence; aspects that often occur is the placement of positions that are not in accordance with educational background and level of competence. Then from the aspect of encouragement to affiliation that is with good cooperation, the problem on the lack of closeness of superiors with subordinates or on fellow co-workers and communication factors.